2021
DOI: 10.14740/jh890
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Survival Patterns of Asian Patients With Relapsed/Refractory Mantle Cell Lymphoma

Abstract: Background Mantle cell lymphoma (MCL) is widely considered an incurable malignancy even with current therapies and relapsed/refractory (R/R) disease to primary treatment remains common. With improved treatment guidelines and the advent of novel agents, patients are increasingly being treated with more lines of regimens. However, outcomes after each line of treatment remain poorly characterized, especially in the Asian population. In this paper, we described the survival outcomes in a group of R/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…All these results showed more sustained and durable survival outcomes over long‐term follow‐ups in R/R MCL patients treated with BTK inhibitors in the early line than in the later lines. These findings hold considerable importance as it is known that the survival outcomes in MCL become worse with every relapse and increasing line of treatment 22 . The previous studies have indicated that the earlier initiated treatment of MCL patients could lead to a survival benefit.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…All these results showed more sustained and durable survival outcomes over long‐term follow‐ups in R/R MCL patients treated with BTK inhibitors in the early line than in the later lines. These findings hold considerable importance as it is known that the survival outcomes in MCL become worse with every relapse and increasing line of treatment 22 . The previous studies have indicated that the earlier initiated treatment of MCL patients could lead to a survival benefit.…”
Section: Discussionmentioning
confidence: 85%
“…These findings hold considerable importance as it is known that the survival outcomes in MCL become worse with every relapse and increasing line of treatment. 22 The previous studies have indicated that the earlier initiated treatment of MCL patients could lead to a survival benefit. Therefore, the optimal place for the initiation of BTK inhibitor therapy in the treatment of patients with R/R MCL to maximize the survival benefits remains a matter of interest.…”
Section: Discussionmentioning
confidence: 99%